Case report of a coronary artery-right ventricular fistula following repeat endomyocardial biopsies in a heart transplant patient. Issue 6 (26th June 2021) - Siebert, Vincent R; John, Alan; Manshad, Ahmad; Darki, Amir
Abstract: Background: Endomyocardial biopsy (EMB) remains the gold standard for cellular rejection surveillance in heart transplant recipients. Coronary artery fistula formation is a rare late and potentially catastrophic complication of repeated endomyocardial biopsies, without contemporary evidence on incidence or management. Case summary: A 47-year-old male was found to have a fistula between his right ventricle and his left anterior descending artery on an angiogram that was performed as a part of regular screening of coronary allograft vasculopathy. Given the low shunt fraction, asymptomatic nature, and lack of guidelines on definitive management, the patient is undergoing conservative management with regular surveillance. Discussion: Coronary artery fistulas were once thought to be rare complications of repeated EMB, but the true prevalence is likely to be higher than previously believed. Ideal treatment and monitoring is unknown given the relative rarity of the condition.